Morphology of Modified Biochar and Its Potential for Phenol Removal from Aqueous Solutions - Komnitsas, Kostas A.; Zaharaki, Dimitra (Frontiers in Environmental Science, 2016)
In the present study, the efficiency of phenol removal from synthetic aqueous solutions by chemically modified biochar with the use of 1M KOH or 1M FeCl3 was investigated. Initially, biochar was produced after slow pyrolysis of three different agricultural wastes, namely pistachio (Pistacia vera L.) shells, pecan (Carya illinoinensis) shells and wood sawdust. The quality of biochar was assessed by evaluating its main properties, such as pH, surface area, porosity and C content. X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used for the identification of biochar’s structure. The efficiency of phenol removal from synthetic solutions was assessed with the use of kinetic and equilibrium experiments. The experimental results show that the KOH-modified biochar exhibited the highest phenol removal efficiency. Hydrophobic sorption on its surface is the main phenol removal mechanism. The pseudo-second order model fits best the kinetic data, while the Freundlich model, as deduced from an equilibrium study describes very well sorption of phenols on all biochars examined.